Chest X-ray Findings in Community-acquired Pneumonia - Marwan Majeed Ibrahim (Wolters Kluwer Medknow Publications, 2024)
Background: Community acquired pneumonia (CAP) is an important subject in pulmonary medicine and chest imaging plays a major role in the diagnosis and chest x ray (CXR) historically are the image of choice in the workup. Aims and objectives: to provide the role of chest X-ray (CXR) in diagnosis of pneumonia. Materials and Methods: This study which involves 185 cases of high clinical probability of CAP investigated by CXR and several patterns of infiltrates has been detected mainly lobar pneumonia followed by interstitial infiltrates then lobular and bronchopneumonic pattern. Chest x ray is not only a tool for diagnosis but also can be utilized in the follow up for resolution or development of complications. Results: CXR is a good modality for pneumonia diagnosis in which lobar pattern of infiltrate was the most common type 82 patient (44.3%), followed by interstitial pattern which was 57 patients (30.8%), then bronchopneumonia pattern 21 patient (11.3%) and lobular pattern 20 patient (10.8%). Conclusions and Recommendations: Chest x ray plays a major role in diagnosis of pneumonia, it can provide information about any structural pulmonary diseases , exclude alternative diagnoses and even giving an idea about the possible underlying pathogen and hence the antibiotic that preferred to be use; so we recommend to use CXR as an initial modality of choice in cases of suspected pneumonia.